PEDAGOGICAL MECHANISMS THAT PROVIDE PROFESSIONAL FORMATION OF FUTURE PHYSICAL EDUCATION TEACHERS THROUGH NATIONAL MOVEMENT GAMES - Alikulov Akmal Akramovich (Bright Mind Publishing, 2025)
This article presents some thoughts on pedagogical mechanisms that provide professional formation of future physical education teachers through national movement games. The use of national games in educational processes and teaching them to perform them independently increases students' interest in the lesson. Students feel creative enthusiasm. At the same time, they get acquainted with our cultural heritage, learn our ancient terms and expressions.
Keywords: Physical education and sports, national active games, future physical education teachers, “Durrа”, “Оtib qоchаr”, “Uchtаlik tо‘ptоsh”, “Xаkkаlаkаm shаrti”, “Оtаmbаqаlа-qоqbоsh”, “Ikki tоsh”, “Chоpiq kulоl”.